Investigation into the influence of treatment parameters using central composite design (CCD) and characterization of chitosan extracted from marine crab shell wastes - Abdulmumuni Sumaila; Jimoh Ibrahim; Muhammad Kabir Yahaya; Ahmed Onimisi Sumaila; Samuel Adamariko Aniki (Universitas Malikussaleh, 2025)
The extraction and characterization of chitosan from marine crab shell waste have garnered significant attention due to the increasing demand for sustainable and biodegradable biomaterials. This study investigates the influence of critical treatment parameters on the extraction efficiency and quality of chitosan, using Response Surface Methodology (RSM) based on Central Composite Design (CCD) for optimization. Marine crab shells, an abundant seafood processing by-product, were subjected to a three-step extraction process involving demineralization, deproteinization, and deacetylation. Key variables such as acid concentration, alkali concentration, reaction temperature, and treatment duration were systematically varied to evaluate their effect on chitosan yield and properties. The optimized extraction conditions yielded high-quality chitosan with improved physicochemical properties. Characterization techniques, including Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA) were employed to assess the functional groups, morphology, crystallinity, and thermal stability of the extracted chitosan. The results confirmed the successful removal of calcium carbonate and proteins, and the presence of characteristic amine and hydroxyl groups indicative of chitosan. SEM analysis revealed a porous surface morphology suitable for biomedical and environmental applications. Statistical analysis of the CCD model showed a significant correlation between the treatment parameters and chitosan yield, with high predictive accuracy (R² > 0.95). This study not only demonstrates the feasibility of utilizing marine crab shell waste as a valuable resource but also highlights the effectiveness of CCD in optimizing biopolymer extraction processes. The findings contribute to the advancement of green chemistry and waste valorization strategies, promoting the circular bioeconomy and environmental sustainability.